Interpretation of Meaning in the Lyrics of a Minangkabau Regional Song with the Title “Pasan Mandeh” (Hermeneutic Study) - Habib, Ikhwanul; Masruri, Hadi (Universitas Pamulang, 2025)
To understand the meaning of a text or work of art can use a hermeneutic approach. This study aims to interpret the meaning in the lyrics of a Minangkabau folk song titled